Decision-making process for maintenance of concrete bridge deck with asphalt overlays using automated digital road scanner. (December 2022) - Lee, Sangyum; Oh, Han Jin; Cho, Byoung Hooi
Abstract: This study proposes a decision-making process for the maintenance of asphalt overlays on concrete bridge decks based on interface conditions evaluated by a non-destructive method. Field data, including crack ratio, rutting depth, surface roughness (IRI, international roughness index), and relative permittivity, were used as variables to evaluate the asphalt bridge-deck pavement conditions at twelve locations (total length of 5268 m) using a vehicle-type automated digital road scanner. The relative permittivities of the concrete bridge decks were measured using a ground penetrating radar scanner on the surfaces of the asphalt layers, and the deck conditions were verified after the removal of the asphalt layers. Through field investigation, 1312 data sets were collected, and statistical analyses were performed to identify characteristics of the variables for evaluating the bridge-pavement condition. Based on the field data and Seoul pavement index formula, the bridge pavement index, which can reflect the condition of the concrete bridge deck beneath the asphalt layer, was developed. Furthermore, a decision-making tree was developed to select appropriate rehabilitation methods depending on various distress types and seriousness, as determined by field data. Highlights: The vehicle type ADRS shows continuous and rapid data collecting performance on the asphalt overlay with minimizing traffic controls. 3D GPR (ground penetrating radar) effectively measures the interface conditions of concrete bridge deck beneath asphalt layers. A BPI formula which can evaluate the performance of asphalt bridge pavement system considering the interface condition between the asphalt layers and concrete bridge deck was proposed. A data-driven decision-making process for the maintenance of asphalt bridge pavement system was suggested for selecting an appropriate rehabilitation method.